A biosytematic [i.e. biosystematic] study of the seven minor genera of the Hyacinthaceae - Van der Merwe, Alison M. (Alison Mary) (Stellenbosch : Stellenbosch University, 2012)
Thesis (DPhil)--Stellenbosch University, 2002.